Influence of the abilities in controlling violence behavior to the length of stay of schizophrenic clients in Bogor mental hospital, Indonesia (Medical Journal of Indonesia, 2009)
Aim In average, the length of hospital stay in mental hospitals in Indonesia is 54 days, the longest of which occur on schizophrenic clients. In Bogor Mental Hospital, the average length of stay is 115 days. Those with schizophrenic and violence behavior have 42 days length of stay. The purpose of this study was to reduce length of stay for schizophrenic clients by enhancing their abilities to control violence behavior. Methods This is a quasi experimental study with multiple series design. Study was conducted in Bogor Mental Hospital with 152 respondents (75 intervention and 77 non intervention). Training was given to the intervention group about the ways how to control violence behavior. Results The results of this study showed that the average length of stay in the hospital for the clients in intervention group was 23 days and non intervention group was 40 days. There were 86.6% of clients in intervention group that independently (without assistance) could control their behavior, whereas 13.4% still need assistant. All clients in non intervention group had no abilities to control their violence behavior. Clients who were independent in controlling violence behavior had significantly shorter length of stay compared to non independent clients (p < 0.05). Conclusion Hence, the training control violence behavior can increase the abilities of the clients in controlling their violence behavior and resulting in shorter length of stay in hospital. (Med J Indones 2009; 18: 31-5) Keywords: violence behavior, schizophrenia, training, length of stay